2007
DOI: 10.1109/tasc.2007.898112
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Results of a 500 m HTS Power Cable Field Test

Abstract: The demonstration and verification tests of a 500 m High-Tc superconducting (HTS) cable were carried out at the CRIEPI laboratory in Yokosuka from March 2004 to March 2005. The HTS cable consisted of a cold dielectric core with nominal capacity of 77 kV and 1 kA that had an HTS shield layer. CRIEPI and Furukawa have conducted tests for investigating the basic properties of the cable and a long-term loading test for confirming 30-year operations. Moreover, we conducted an "over-loading test" and a "cooling syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Today, researchers and manufacturers worldwide are continuously developing and testing prototype HTS power lines [2][3][4][5][6][7]. Studies have been carried out both on laboratory facilities with short cables (tens of metres) and on large industrial facilities with long cables (several kilometres).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, researchers and manufacturers worldwide are continuously developing and testing prototype HTS power lines [2][3][4][5][6][7]. Studies have been carried out both on laboratory facilities with short cables (tens of metres) and on large industrial facilities with long cables (several kilometres).…”
Section: Introductionmentioning
confidence: 99%
“…With increasing pressure, the specified range is extended (at two bars, the operating range is 20.6 K), but the increase in temperature leads to a significant reduction of the critical current. For example, paper [6] reported that tests on 500-m HTS cables, created during the Japanese super-ACE project, showed that the critical current value fell from 2290 A to 1570 A when the liquid nitrogen temperature was increased from 69 K to 77 K. For short cables, one can always choose a nitrogen flow rate in order to ensure that the temperature difference is not greater than a predetermined value, even with significant heat gain through the insulation. The resulting pressure losses are small (because of the short channel length), so the problem of the hydraulic resistance of the channel does not matter.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the development of high temperature superconductors (HTS), the SC-PT system can use liquid nitrogen (LN2) as coolant, which makes the SC-PT system using HTS practical. Recently, several practical projects of the AC SC-PT system have started or been planned in the world [1]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their low loss property compared with copper cables, they are constructed, tested in power grids [1][2][3][4] and investigated analytically in terms of magnetic field and AC loss considerations [1][2][3][4][5][6][7][8][9], especially for single phase cable architecture. Recently, a tri-axial cable composed of three concentric phases has been intensively developed since it reduces the amount of used HTS tapes and produce small leakage field and low heat loss in comparison with other three phase HTS cables.…”
Section: Introductionmentioning
confidence: 99%